Biocharcoal dari Biji Salak (Salacca edulis) sebagai Adsorben Terhadap Kromium - Pongenda, Rudy Christiyanto; Napitupulu, Mery; Walanda, Daud K. (Universitas Tadulako, 2015)
Salak, snake skin fruit, is one of many kind fruit that is much preferred by people because its taste is sweet, crunchy and because it has a high nutrient content and have good prospects for cultivated. During this time, only flesh fruit of salak are utilized and the seed become waste. Therefore, it has been done a research about biocharcoal of salak seed (salacca edulis) as an absorbent for chromium. The method used in this study was a laboratory experiment using salak seeds biocharcoal as the adsorbent for chromium, concentration of absorbed chromium was measured by using a spectrodirect spectrophotometer. The results showed that the optimum time for adsorption of metal ion chromium obtained was 60 minutes with the absorption efficiency of 99.67%, while the optimum weight for absorption of metal ion chromium obtained was 80 mg with the absorption efficiency of 99.70% and the optimum concentration for absorption of metal ion chromium was 80 ppm with the absorption efficiency of 99.77%.